2018
DOI: 10.1242/jeb.163717
|View full text |Cite
|
Sign up to set email alerts
|

The fallacy of thePcrit – are there more useful alternatives?

Abstract: P critgenerally defined as the P O2 below which the animal can no longer maintain a stable rate of O 2 consumption (Ṁ O2), such that Ṁ O2 becomes dependent upon P O2provides a single number into which a vast amount of experimental effort has been invested. Here, with specific reference to water-breathers, I argue that this focus on the P crit is not useful for six reasons: (1) calculation of P crit usually involves selective data editing; (2) the value of P crit depends greatly on the way it is determined; (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 69 publications
6
78
0
1
Order By: Relevance
“…This variability occurred even though P crit trials were conducted after > 24 h fasting, after 8-12 h since transferring fish to the respirometer, and during the dark phase of the photoperiod, when this species is less active. Owing to the variability of M O2 at high P O2 , the use of BSR is frequently coupled with removal of M O2 data points that fail to meet certain criteria (see Claireaux and Chabot, 2016 and Wood, 2018 for examples). This practice has raised concern over the rationale and validity of applying data selection criteria (Claireaux and Chabot, 2016; Wood, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This variability occurred even though P crit trials were conducted after > 24 h fasting, after 8-12 h since transferring fish to the respirometer, and during the dark phase of the photoperiod, when this species is less active. Owing to the variability of M O2 at high P O2 , the use of BSR is frequently coupled with removal of M O2 data points that fail to meet certain criteria (see Claireaux and Chabot, 2016 and Wood, 2018 for examples). This practice has raised concern over the rationale and validity of applying data selection criteria (Claireaux and Chabot, 2016; Wood, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the variability of M O2 at high P O2 , the use of BSR is frequently coupled with removal of M O2 data points that fail to meet certain criteria (see Claireaux and Chabot, 2016 and Wood, 2018 for examples). This practice has raised concern over the rationale and validity of applying data selection criteria (Claireaux and Chabot, 2016; Wood, 2018). In addition, direct comparisons of BSR with various non-linear regression approaches have shown that BSR is seldom the best model to fit M O2 data across a range of P O2 (Marshall et al, 2013; Cobbs and Alexander, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of some fish species showed that the P crit was positively correlated with resting metabolism (Fu et al, ; Mandic et al, ) and, thus, suggested that a low resting metabolism potentially facilitates hypoxia tolerance (Killen et al, ). This might be because EPOC h is an inappropriate indicator of hypoxia tolerance (as P crit might also be; see details in the next paragraph, Wood, ), as we mentioned in the introduction. In this study, no significant relationship was observed between the RMR h and LOE at the interspecific level (Figure d).…”
Section: Discussionmentioning
confidence: 99%